2023
DOI: 10.1039/d3ta05726g
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous upcycling of PET plastic waste and CO2 reduction through Co-electrolysis: a novel approach for integrating CO2 reduction and PET hydrolysate oxidation

Sravan Kumar Kilaparthi,
Ahmed Addad,
Alexandre Barras
et al.

Abstract: The paper reports on the concurrent electrochemical generation of formate through CO2 reduction (cathode) and polyethylene terephthalate (PET) hydrolysate oxidation (anode).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…33 Likewise, Kilaparthi et al also reported a 200 mV lower anodic potential for PET-hydrolysate-derived EGO compared to OER at 20 mA/cm 2 by employing CuCoO@rGO as an anode. 49 1 H NMR analysis (Figure S18a) of the PET hydrolysate before electrolysis indicates the complete alkaline hydrolysis of PET to its monomers, namely EG and terephthalic acid (TPA). Controlled potential electrolysis of the PET hydrolysate shows a decrease in the current density expected from EG consumption (Figure S18b).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…33 Likewise, Kilaparthi et al also reported a 200 mV lower anodic potential for PET-hydrolysate-derived EGO compared to OER at 20 mA/cm 2 by employing CuCoO@rGO as an anode. 49 1 H NMR analysis (Figure S18a) of the PET hydrolysate before electrolysis indicates the complete alkaline hydrolysis of PET to its monomers, namely EG and terephthalic acid (TPA). Controlled potential electrolysis of the PET hydrolysate shows a decrease in the current density expected from EG consumption (Figure S18b).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Further, the oxidation products were analyzed using 1 H and 13 C NMR, and it was found that the highest FE of 85.7% was obtained at a potential of 1.5 V at the anode whereas 97.4% at the cathode. 329 Further, two-electrode electrolyzer (CuCoO@r-GO∥BOC@rGO) was utilized for the coproduction of formic acid by the CO 2 RR and EG oxidation. Also, a very low potential of 1.9 V was required to achieve a current density of 10 mA cm −2 .…”
Section: Electrocatalytic Plastic Upcyclingmentioning
confidence: 99%
“…Meanwhile, FE greater than 130% was obtained over a potential ranging from 1.7 to 2.1 V. As a result, this integrated strategy not only provides an effective solution for valuing PET plastic trash but also it may open the way for the cost-effective and long-term manufacturing of value-added commodity chemicals from plastic waste while also reducing CO 2 emissions. 329 Due to its harmful impact on the ecosystem and ecology, microplastic contamination has become a critical environmental issue of global concern. It is extremely difficult to suggest a more economical strategy to achieve highly selective conversion of microplastic into add-value products due to their characteristics of complicated composition.…”
Section: Electrocatalytic Plastic Upcyclingmentioning
confidence: 99%
See 2 more Smart Citations